EFFECT OF NUTRIENT MANAGEMENT USING AQUA-FERTILIZATION ON YIELD, QUALITY AND NUTRIENT UPTAKE OF WHEAT (TRITICUM AESTIVUM L.) UNDER DRYLAND CONDITIONS - BARETH, VISHNU Singh; Singh, R.K.; PARIHAR, C.M (Annals of Agricultural Research, 2014)
A field experiment was conducted at Indian Agricultural Research Institute, Research Farm, NewDelhi during rabi 2001 and 2002. The data reveals that application of nitrogen upto 60 kg/ha has significantly increased grain and straw yields, harvest index, nitrogen and phosphorus content and their uptake and protein yield. Similarly placement of FYM either alone or in combination with urea significantly increased the above parameters over no FYM application. Combined application of urea and FYM proved better than their sole application. Combined use of 60 kg N through urea + 6 t FYM/ha proved better than equal dose of 90 kg N/ha supplied through urea. Aquafertilization with water volume upto 30,000 lit/ha has significantly increased above parameters over dry sowing.